RAJA MATARAM DAN PERANANNYA DALAM DUNIA KARAWITAN - Rabimin Rabimin (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2006)
The idea of this article was from the author ~ thought to find out about the values within the Javanese karawitan. Appart from that it is also connected to the careness to nowadayÂ cÂ fenomenon that young generation is careless of those values. They are more interested in the skill ofplaying gamelan instead, wich is relatively easier to do. Through a research on â€œSerat Till Asrfâ€ by Supardal Hardasukarta, particularly on Asmarandana and Mijil Parts, it is known that they convey the activities of King Adiningrat Anyakrawati in Mataram studying karawitan seriously. The result of the analysis shows that after having failed to expand the kingdom teritory, he realized the importance of karawitan functions and values to Javaneseâ€™ lives. To understand deeper meaning of karawitan, he asked Sunan Kalijaga to explain the knowledge of reality within karawitan. He later realized that the knowledge of reality leads to the lesson of good manner as a way of live, both during the 4fe and after the death. The impact of that he then wrote aÂ book called â€œSastra Gendingâ€ as a part of the Sophisticated Karawitan.KeywordsÂ : Meaning of Karawitan.